2005
DOI: 10.1115/1.1831294
|View full text |Cite
|
Sign up to set email alerts
|

A Second Look at the Higher-Order Theory for Periodic Multiphase Materials

Abstract: In this communication, we present a reformulation, based on the local/global stiffness matrix approach, of the recently developed higher-order theory for periodic multiphase materials, Aboudi et al. [“Linear Thermoelastic Higher-Order Theory for Periodic Multiphase Materials,” J. Appl. Mech., 68(5), pp. 697–707]. This reformulation reveals that the higher-order theory employs an approximate, and standard, elasticity approach to the solution of the unit cell problem of periodic multiphase materials based on dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…Homogenization 1 Ten years ago, a new generation of heterogeneous materials, called functionally graded materials, appeared in the mechanical literature (see e.g. [1], [2], [3], [4] and [11]). These materials, characterized by high resistance to loading and/or to temperature increase, have been studied intensively, and numerical homogenization formulas have been proposed under the assumption of smoothly varying fields, which means that the different components of these materials are supposed to be perfectly bonded by thermomechanical processing in order to exhibit continuously changing properties.…”
Section: ë òóý º ëø ò ö × ùø ñ ð øó ñ ¸ α < X < B¸0 < T < T¸ømentioning
confidence: 99%
“…Homogenization 1 Ten years ago, a new generation of heterogeneous materials, called functionally graded materials, appeared in the mechanical literature (see e.g. [1], [2], [3], [4] and [11]). These materials, characterized by high resistance to loading and/or to temperature increase, have been studied intensively, and numerical homogenization formulas have been proposed under the assumption of smoothly varying fields, which means that the different components of these materials are supposed to be perfectly bonded by thermomechanical processing in order to exhibit continuously changing properties.…”
Section: ë òóý º ëø ò ö × ùø ñ ð øó ñ ¸ α < X < B¸0 < T < T¸ømentioning
confidence: 99%
“…Then, using (81), (76), (78), (11), (77), we obtain (4), (5), (6), where g is defined by (7). We assume that the material is non-homogeneous, in the sense that all material parameters depend on the coordinates x and y.…”
Section: Appendix Amentioning
confidence: 99%
“…Recently, Bansal and Pindera [6,7] have shown that the "higher-order theory", introduced in [2,3] for functionally graded materials, is in fact a simple finite-volume direct averaging micromechanics approach. These materials are expected to show superior properties for high temperature resistance.…”
mentioning
confidence: 99%
“…This method can of course be used to "tailor" (design) new materials with enhanced properties by averaging in a clever (but very heterogeneous) way simple phases. It has been often described (and sometimes revisited) in the mechanical literature and here again giving a complete list is impossible; let us mention Suquet (1982), Francfort, Leguillon and Suquet (1983), Francfort, Nguyen andSuquet (1983), Hashin (1983), Suquet (1983), Maugin (1992), Aboudi et al (1999), Ghosh et al (2001), Bansal and Pindera (2003), Michel and Suquet (2004), Alshirts and Maugin (2005), Bansal and Pindera (2005), Bardzokas and Zobnin (2005), Guinovart-Diaz et al (2005), Suquet (2005), Idiart et al (2006)). In particular, the concept of "homogeneous equivalent continuum" (Maugin (1992)) has been used to predict the macroscopic response from microscopic analyses by replacing the macroscopic heterogeneous medium, represented by an element called "representative volume element", by a continuum model (see Van der Sluis et al (1999), where a numerical homogenization technique has been proposed, which offers the possibility to determine the effective properties of a viscoplastic constitutive model).…”
Section: Introductionmentioning
confidence: 99%